PENGARUH METODE LATIHAN GLOBAL DAN ELEMENTER TERHADAP KEMAMPUAN PASSING ATAS ATLET BOLAVOLI - Syafira Halimah; Yogi Arnaldo Putra; Hermanzoni; Eko Purnomo (JURNAL ILMU KEOLAHRAGAAN, 2026)
This research stems from the fact that the achievements achieved so far have not been optimal. The weakness is that players have not mastered the volleyball overhead pass. This study aims to see the effect of global and elementary training methods on the ability of the overhead pass. This type of research is a quasi-experimental. The population in this study were students who participated in volleyball training at VAC. Solok-Selatan, totaling 25 people. The sample in this study was taken using a propusive sampling technique, namely with certain considerations. The researcher determined the sample to be taken as many as 10 male volleyball athletes from VAC. Solok-Selatan. The research instrument used the overhead pass test. Statistical data analysis techniques used the Liliefors normality test and t-test with a significance level of ɑ = 0.05. The results of this study indicate that there is an effect of the global training method on the ability of the overhead pass of male volleyball athletes VAC. Solok-Selatan, obtained T table of 0.002 <0.05. There is an effect of the elementary training method on the passing ability of male volleyball athletes VAC. In Solok-Selatan, the T-table was 0.001 < 0.05. There was a difference between the global and elementary training methods on the ability to pass overhead. The elementary training method had a greater effect on the ability to pass overhead in male volleyball athletes in VAC than the global training method. In Solok-Selatan, the T-table was 0.019 < 0.05.